Prognostic significance of blood pressure variability on beat-to-beat monitoring after transient ischemic attack and stroke - Webb, A; Mazzucco, S; Li, L; Rothwell, P (American Heart Association, 2017)
Background and Purpose: Visit-to-visit and day-to-day BP-variability (BPV) predict an increased risk of cardiovascular events, but only reflect one form of BPV. Beat-tobeat BPV can be rapidly assessed and might also be predictive. Methods: In consecutive patients within 6 weeks of TIA or non-disabling stroke (Oxford Vascular Study), BPV (CV, coefficient of variation) was measured beat-tobeat over 5 minutes (Finometer), day-to-day over 1 week on home monitoring (HBPM, 3 readings, 3 times daily) and on awake ambulatory BP monitoring (ABPM). BPV after 1 month standard treatment was related (Cox proportional hazards) to recurrent stroke and cardiovascular events over 2-5 years, adjusted for mean SBP. Results: Among 520 patients, 26 had inadequate beat-to-beat recordings and 22 patients were in AF. 405 patients had all forms of monitoring. Beat-to-beat BPV predicted recurrent stroke and cardiovascular events independently of mean SBP (HR per group SD, stroke: 1.47, 1.12-1.91, p=0.005; cardiovascular events: 1.41, 1.08-1.83, p=0.01), including after adjustment for age and gender (stroke 1.47,1.12- 1.92, p=0.005) and all risk factors (1.40,1.00-1.94, p=0.047). Day-to-day BPV was less strongly associated with stroke (adjusted HR=1.29, 0.97-1.71, p=0.08) but similarly with cardiovascular events (1.41, 1.09-1.83, p=0.009). BPV on awake ABPM was non-predictive (stroke 0.89, 0.59-1.35, p=0.59; cardiovascular events 1.08, 0.77-1.52, p=0.65). Despite a weak correlation (r=0.119, p=0.02), beat-to-beat BPV was associated with risk of recurrent stroke independently of day-to-day BPV (1.41, 1.05-1.90, p=0.02). Conclusions: Beat-to-beat BPV predicted recurrent stroke and cardiovascular events, independently of mean SBP and risk factors, but short-term BPV on ABPM did not. Beat-to-beat BPV may be a useful additional marker of cardiovascular risk.